Cyclea barbata L. Miers.: Penggunaan tradisional, fitokimia, dan aktivitas farmakologi - Surya Febrianto; Fradnya Vrianka Praharsini; Zulfiana Fitrianingrum Annas; Nisa Isneni Hanifa (Universitas Mataram, 2022)
Indonesian people still favor the use of traditional medicine because they believe its side effects are lower than synthetic drugs. One of the plants that can be used in traditional medicine is Cyclea barbata L. Miers, or green grass jelly. This study aimed to explain and summarize the traditional use, phytochemical content, and pharmacological activity of C. barbata. All information on C. barbata was collected from various electronic databases (Google Scholar, Science Direct, and PubMed) using important and related keywords. Secondary metabolites found in stems, roots, and leaves are alkaloids and flavonoids. The pharmacological activities of C. barbata include antibacterial, antioxidant, anti-plasmodial, immunomodulator, Alzheimer, anti-inflammatory, anti-cholesterol, and antiulcer. Although C. barbata has been used empirically, further research is still needed to ensure the effectiveness and safety of this plant.